STRATEGIC IMPOLITENESS IN TELEVISED POLITICAL DEBATES: TOWARDS AN INTEGRATIVE MODEL OF MEDIA-MEDIATED POLITICAL COMMUNICATION - Sriwati Sriwati; Dadang Sudana; Wawan Gunawan; Mulyana Agung; Yulianto Erwin (University of Kuningan, 2026)
This study examines strategic impoliteness in Indonesian televised political debates, focusing on how language use shapes political communication and public perception in media-mediated interactions. Previous studies on political discourse have largely emphasized persuasion and politeness, while limited attention has been devoted to systematic analyses of impoliteness in televised political debates, particularly within the Indonesian context. This study addresses this gap by analyzing the forms and functions of impoliteness strategies and their implications for political image construction. Using a qualitative approach with pragmatic and sociopragmatic analysis, the study investigates 70 utterance segments containing face-threatening acts (FTAs) drawn from three televised talk show episodes: Indonesia Lawyers Club (2016; 2023) and Mata Najwa (2019). The analysis applies Culpeper’s impoliteness framework, encompassing bald on record impoliteness, positive impoliteness, negative impoliteness, mock politeness/sarcasm, and withholding politeness. The findings demonstrate that televised political debates are inherently face-threatening due to argumentative competition, media performance pressure, and ideological polarization. All five impoliteness strategies were identified, with positive impoliteness and bald on record impoliteness emerging as the most dominant strategies, each accounting for 21.4% of the total occurrences. The study further reveals that the impact of impoliteness on politicians’ public image is ambivalent, depending on audience ideology and group identification. Finally, this study proposes an integrative model linking communicative context, impoliteness strategies, and political image formation within media-mediated political discourse.